QUALITY RISK MANAGEMENT IN THE PHARMACEUTICAL INDUSTRY IN THE MANUFACTURING PROCESS OF NON STERILE NON BETA-LACTAM ORAL SOLID & LIQUID DOSAGE FORM WITH FMEA METHOD - Lamsihar Siagian, Widya
The pharmaceutical industry plays a vital role in Indonesia's industrial landscape. In its business operations, companies must produce high-quality, safe, secure medicines that can be maintained consistently. However, carrying it out is certainly not free from risks. In the pharmaceutical industry, especially in the pharmaceutical preparation production process, every product produced throughout its life cycle (product life cycle) will still have potential risks even though it has implemented GMP (Good Manufacturing Practices). Risks include safety, efficacy, quality, raw material suppliers, and others. In the context of risk management in the production area where the author does this research, the risk assessment approach that is currently emerging is still general, only from common pharmaceutical dosage forms, and needs to be carried out comprehensively. This condition can be caused by the absence of a complete risk management design and measuring tools to assess the current risk condition. Considering the potential risks that might arise at each stage of the production process for each product, these risks must be analyzed, and their impact must be evaluated. This situation is because each product generally has different characteristics and profiles. This research aimed to create a Quality Risk Management design for products using the FMEA (Failure Mode Effect Analysis) method, determine the Priority ActionMatrix, and calculate the Risk Management Index (RMI) from the backbone Pareto product representatives for Oral Solid, Liquid non-sterile non-Betalactam preparations in industrial pharmacies. The research began with grouping products based on therapeutic class, determining selected products, preparing the process flow from the process activity stages, and preparing Quality Attributes, which was continued with creating Quality Risk Management (QRM) and determining Priority Actions. Risk matrix with Risk Priority Number (RPN) > 20 (according to management policy) and finally, calculate %RMI. In this research, a comprehensive quality risk management design was obtained for Phenytoin Sodium 100 mg capsules, resulting in a total of 95 quality risks, with 73 risks at a low level (76.8%), 20 risks at a medium level (21.1%), and 2 risks at a high level (2.1%). For the Cough Syrup DEF*100 ml, there were a total of 123 risks identified, with 96 risks at a low level (78%), 25 risks at a medium level (20%), and 2 risks at a high level (2%). From the design of the Priority Action Matrix, a risk improvement mitigation plan was obtained for 100 mg Phenytoin Capsules with 33 Action Plans and 36 Action Plans for DEF*100 ml Cough Syrup product, respectively. Furthermore, the %RMI was obtained at 89%. The QRM design created could produce risks according to the flow.process stages determined for 100 mg Phenytoin Capsules and 100 ml DEF* Cough Syrup. By the determined Priority Action Matrix, the improvement mitigation plan for the two products will be carried out within a specified implementation time limit, and the person in charge will control the plan. The calculation of the % RMI obtained showed that QRM for backbone and Pareto products is generally reasonable. However, further attention is still needed to complete the improvement mitigation plan that has not been carried out in order to achieve an excellent minimum percentage value in each parameter assessed and also the need for top management attention in further investment in order to obtain a more excellent % RMI for the company.